Using WhatsApp for co-creation of learning resources: A case of a South African university - Rambe, Patient; Chipunza, Crispen; Ng’ambi, Dick (The Journal for Transdisciplinary Research in Southern Africa Vol. 16, No. 1, 2020)
Although culturally diverse students have potential to create enriched learning resources, it is difficult to harness students’ agency and to aggregate individual contributions into a meaningful learning resource. This is one of the challenges facing higher education institutions in South Africa where institutions are increasingly cosmopolitan and culturally diverse, but production of knowledge has largely remained skewed in favour of those students with unlimited access to learning resources, the Internet and peer networks, anywhere, anytime. Although the appropriation of emerging technologies such as mobile phones has enabled a digital sharing culture, this social practice has not been harnessed for co-creation of learning resources. This article reports on a study that sought to uncover the extent to which the use of WhatsApp-enabled phones facilitated the co-creation of learning resources in a human resource management programme at a university of technology in South Africa. The article employed Amartya Sen’s capabilities framework to analyse WhatsApp interactions of 72 participants from underprivileged backgrounds. The article concludes that leveraging students’ capabilities, including rich culturally diverse knowledge, is not a mere outcome of access to a tool such as WhatsApp, but requires pedagogical designs that exploit the affordances of the tool.
Research Article
Keywords: WhatsApp; MIM; Collectively generated resources; Dialogic interactions; Learning resources